Guidelines for endoscopic submucosal dissection and endoscopic mucosal resection for early gastric cancer. Issue 1 (4th October 2015) - Ono, Hiroyuki; Yao, Kenshi; Fujishiro, Mitsuhiro; Oda, Ichiro; Nimura, Satoshi; Yahagi, Naohisa; Iishi, Hiroyasu; Oka, Masashi; Ajioka, Yoichi; Ichinose, Masao; Matsui, Toshiyuki
Abstract : In response to the rapid and wide acceptance and use of endoscopic treatments for early gastric cancer, the Japan Gastroenterological Endoscopy Society (JGES), in collaboration with the Japanese Gastric Cancer Association (JGCA), has produced 'Guidelines for ESD and EMR for Early Gastric Cancer', as a set of basic guidelines in accordance with the principles of evidence‐based medicine. These Guidelines cover the present state of knowledge and are divided into the following seven categories: Indications, Preoperative diagnosis, Techniques, Evaluation of curability, Complications, Long‐term postoperative surveillance, and Histology. Twenty‐three statements were finally accepted as guidelines, and the majority of these were obtained from descriptive studies with lower evidence levels. A number of statements had to be created by consensus (the lowest evidence level), as evidence levels remain low for many specific areas in this field.